The many meanings of neo-feudalism Analysis of academic and public discourse alluding premodern social structures - István Kollai (Köz-gazdaság, 2020)
The essay intends to analyse those strands within Hungarian public discourse which allude – either negatively or positively – medieval hierarchy when discussing present political, social or cultural tendencies. This discourse includes both the critical views of academic sphere towards personal dependencies within capitalism – calling frequently, but not regularly neo-feudalism or feudal-capitalism – and the possible nostalgic sentiments from the side of political rhetoric or publicity towards an ‘ancient régime’. This analysis on neo-feudalism raises the dilemma, whether the binary dichotomy of democracy-authoritarianism could be the adequate axis where Central-Eastern European societies’ ‘transition fatigue’ can be scrutinized? Neo-feudal discourse elucidates another axis of modernization-traditionalism: what is questioned by some elite groups and their supporters is not democracy but modern institutions, whose pivotal role is attempted to be replaced by personal dependency and personalized coordination of society.